1994
DOI: 10.12693/aphyspola.85.849
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Triglycine Sulphate Crystals Admixtured with L-Threonine

Abstract: The influence of L-threonine admixture on the dielectric properties of triglycine sulphate (TGS) crystals was studied. With increasing concentration of the admixture in the solution from which the crystals were grown, their maximum permittivity and spontaneous polarization were found to decrease, their Curie point was found not much different than that for pure TGS crystals (322 K), the coercive field and bias field increased. The domain structure of the obtained crystals was also studied by the liquid crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Similar studies for TGS crystals admixtured with L-a-alanine were reported earlier [12]. This study is a continuation of the studies on the effect of L-threonine, an amino acid of the chemical formula CH 3 CH(OH)CHNH 2 COOH which differs from glycine by the presence of a C±CH 3 (OH) group, on single crystals of TGS, reported earlier [13,14].…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…Similar studies for TGS crystals admixtured with L-a-alanine were reported earlier [12]. This study is a continuation of the studies on the effect of L-threonine, an amino acid of the chemical formula CH 3 CH(OH)CHNH 2 COOH which differs from glycine by the presence of a C±CH 3 (OH) group, on single crystals of TGS, reported earlier [13,14].…”
Section: Introductionsupporting
confidence: 82%
“…The temperatures of these maxima depend not only on the frequency of the measuring field but also on whether the sample was in an external electric field and whether it was characterised by a bias field E b . The crystals of L-a-alanine [12] and Lthreonine [13,14] which have the bias field, do not show a maximum of e in this temperature range. A sample of TGS + 20% L-threonine characterised by the highest value of E b also did not show a maximum of e in the range from 130 to 210 K.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…It should be noted that the influence of the ageing process on the domain structure dynamics has been examined in doped triglycine sulphate [6] and (CH3NH3) 5 Bi2 Br11 [7] crystals.…”
Section: Resultsmentioning
confidence: 99%